Pengaruh Kompensasi, Analisis Jabatan dan Pola Pengembangan Karir Terhadap Kinerja Karyawan - Muhammad Fizdian Arismunandar; Hazmanan Khair (Magister Manajemen Universitas Muhammadiyah Sumatera Utara, 2020)
The purpose of this study was to determine the effect of compensation, job analysis and career development patterns on employee performance at PT. Angkasa Pura II (Persero) Kualanamu Branch Office. This research uses an associative approach. The population and sample of this research are employees at PT. Angkasa Pura II (Persero) Kualanamu Branch Office Electrical and Mechanical Facility Division totaling 65 people. Data collection techniques used in this study were interviews and questionnaires. Meanwhile, the data analysis technique used multiple linear regression analysis. The results showed that partially compensation did not have a significant effect on employee performance. Partially, job analysis has a significant effect on employee performance. Partially, career development patterns have a significant effect on employee performance. Simultaneously compensation, job analysis and career development patterns have a significant effect on employee performance at PT. Angkasa Pura II (Persero) Kualanamu Branch Office.